1927 nm Thulium Laser Successfully Treats PostInflammatory Hyperpigmentation in Skin of Color - Mana Abdullah Alharbi (Hindawi Limited, 2021)
Background. Treatment of postinflammatory hyperpigmentation (PIH) in patients with dark skin is challenging as the treatment itself might provoke paradoxical PIH. Only few studies examined the safety and efficacy of nonablative laser treatment in these patients. The objective was to examine efficacy and safety of nonablative 1927 nm wavelength laser followed by bleaching creams in the treatment of PIH. Methods. It was a prospective interventional pilot study that was conducted during 2019. All patients were of Fitzpatrick skin type IV who had unsatisfactory response to topical bleaching creams used for at least three months. Patients received one to four sessions of laser treatment (6 weeks apart) followed by topical hydroquinone 4% cream twice daily for 6 weeks. Improvement was assessed by two blinded independent dermatologist evaluators. Results. A total of nine patients were enrolled and the outcome could not be assessed in one patient who was lost for follow-up. The affected sites were the abdomen, face, and other body parts. Three of the eight evaluated patients had excellent response (37.5%), four had satisfactory response (50.0%), and one had nonsatisfactory response (12.5%). The downtime was manifested as edema and erythema that disappeared after 5 to 7 days. Improvement was more evident in first session and it declined in subsequent sessions. None of the patients had paradoxical pigmentation after treatment. Conclusions. Low energy low density nonablative fractional 1927 nm wavelength laser treatment followed by topical hydroquinone 4% cream for 6 weeks is a safe and effective modality for improving PIH in patients with darker skin types.